Job Satisfaction and Well-Being of Care Aides in Long-Term Care During the COVID-19 Pandemic: A Comprehensive Literature Review - Maryam Sarfjoo Kasmaei; Shannon Freeman; Davina Banner; Tammy Klassen-Ross; Melinda Martin-Khan (World, 2025)
The COVID-19 pandemic greatly impacted care aides in long-term care facilities (LTCFs), exacerbating existing challenges and introducing new stressors that profoundly affected their job satisfaction, mental health, and overall well-being. This study investigates these multifaceted effects by conducting a comprehensive literature review of 18 studies from 2020 to 2023 across multiple countries. The findings reveal that care aides, mostly older and female and often immigrants with limited formal education, faced increased workloads, emotional exhaustion, physical fatigue, anxiety, and heightened stress levels during the pandemic. These factors led to decreased job satisfaction, higher burnout rates, and further pressure on LTCFs. The review emphasizes the need for strong support systems and targeted interventions, including mental health resources, counseling, adequate personal protective equipment (PPE), effective workload management, professional development opportunities, fair compensation, and supportive work environments. Addressing these issues is crucial for maintaining a stable and effective LTC workforce, improving care outcomes for residents, and enhancing the healthcare system’s resilience against future challenges.